Studies on Cellulose Hydrolysis and Hemicellulose Monosaccharide Degradation in Concentrated Hydrochloric Acid - Li, Yan (Université d'Ottawa / University of Ottawa, 2014)
Given the volatile, generally high price of crude oil, as well as environmental concerns associated with its use as a fuel, development of alternative energy sources is currently of considerable interest. Lignocellulose-derived energy has the potential to supplant traditional fossil fuels in the future because of its economic and environmental advantages. Lignocellulosic biomass is abundant and renewable. Lignocellulose is primarily composed of cellulose, hemicellulose and lignin, which can be converted by acid hydrolysis to simple sugars used in fermentation to produce biofuels. In this study, hemicellulose was hydrolyzed with different concentrations of hydrochloric acid at different temperatures. The resulting components were analyzed by high performance liquid chromatography (HPLC). The hydrolysis of cellulose was similarly characterized, with two additional parameters, the degree of polymerization (DP) and the crystallinity index (CrI), which were analyzed by Ubbelohde viscometer and X-ray diffraction respectively. The experimental results indicate that the hydrolysis rate of hemicellulose and the generation rate of furfural and 5-hydroxymethylfurfural (HMF) increased with increasing hydrochloric acid concentrations and reaction temperatures. In the selected five monosaccharides, xylose, glucose, mannose, arabinose and galactose, xylose has the highest hydrolysis rate and the accumulation of furfural during xylose hydrolysis is also the highest. Moreover, the hydrolysis rate of cellulose and the generation rate of glucose also increased with increasing hydrochloric acid concentrations and reaction temperatures. DP and CrI, both decreased when the cellulose was treated in concentrated hydrochloric acid. The rate of change of DP increased with the concentrations of acid and the reaction temperatures. The change rate of CrI increases by increasing concentration of acid and the temperature when it is above 0℃, while the CrI index decrease sharply when the reaction temperature was kept below 0℃. Experimental results also show that the hydrolysis rate of cellulose is much lower than that of hemicellulose.
Keywords: cellulose; hemicellulose monosaccharide; hydrolysis; hydrochloric acid; furfural; 5-hydroxymethylfurfural